Intra- and postoperative electrode impedance of the straight and Contour arrays of the Nucleus 24 cochlear implant: relation to T and C levels. - van Wermeskerken GKA; van Olphen AF; Smoorenburg GF (International Journal of Audiology, 2006)
The objective of this study was to investigate electrode impedance in cochlear implant recipients in relation to electrically evoked stapedius reflex measurements during surgery, and to electrode design, stimulation mode, and T and C levels over a nine month period after surgery. Seventy-five implant recipients, implanted with a Nucleus straight electrode array or a Contour array, were included. The results show that: (1) during surgery electrode impedance decreases markedly after electrically evoked stapedius reflex measurements, (2) after surgery, during the period without stimulation until speech processor switch-on, impedance increases, (3) after processor switch-on impedance decreases. The lower impedance values after a period of stimulation are found at the higher T and C levels. Impedances of the straight array electrodes are lower than those of the Contour array. The difference corresponds mainly to their respective surface areas. In addition, the straight array shows a larger increase of impedance in the apical direction than the Contour array, probably because of the larger fluid environment around the basal electrodes of the straight array.